PENGARUH PENDIDIKAN, PENGALAMAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT RAJAWALI NUSINDO MATARAM - Wija Robbiantara; Irianto Irianto; Ahmad Bairizki (Kompeten: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of education, work experience and organizational commitment on employee performance at PT Rajawali Nusindo Mataram. The population of this study were employees at PT Rajawali Nusindo Mataram, the data of this study were obtained by interviews, observations, and questionnaires. This research is associative type by using classical assumption test and multiple linear regression analysis. Based on the t test, it shows that the education variable has a partially insignificant effect on the performance variable, with a value of (-2,680) <1.703. The work experience variable has a partially significant effect on the performance variable, with a value of 4.632>1.703. Meanwhile, the organizational commitment variable has a partially significant effect on the performance variable, with a value of 3.096>1.703. Based on the F test, it shows that the variables of education, work experience and organizational commitment have a significant effect simultaneously on employee performance variables, with a value of 18.491 > 2.96. Based on the beta test, it shows that the work experience variable has the highest value of 0.543 compared to the variable education and organizational commitment